Principles of improvisation and analysis of Johan Christoph Lauterbach’s Cadenza for Mozart’s Aria L’Amero Saro Costante from Opera IL Re Pastore / Nurfarhana Abu Bakar - Abu Bakar, Nurfarhana (2013)
In order for composers to fully express their piece of music, they will need a medium to complete their work. This is where the role of performers comes to play. The responsibility of a performer is to understand and preserve the work of a composer so that their interpretations can be captured by the audience in their performance. Many composers tend to shape the musicians' interpretation of their work but however, most of the composers are deceased and can no longer show the insight of the performance of their compositions. In this matter, musical research and hours of practice is very crucial for a performer, not only to deliver the best performance but more important, to conserve the work of the composers. Sadly, the most common error in a performance today lays in the style of a performer's cadenzas nowadays. This problem occur when a performer produce a set of virtuosity that completely change the originality of a composer's era and style. In other words, performers overly improvisations had given a massive effect to the piece, making it less enjoyable and hard to listen by the audiences. Joachim Quantz, writing over two centuries ago, seems to address the current situation: If none are made it is considered a great defeat, even though many performers would conclude their pieces with more credit without them. Meanwhile, all those who occupy themselves with singing or playing solos want to, or must, make cadenzas. And since their nature and proper way to perform them are not well known, the fashion generally becomes a burden (Quantz, 1966).